Development of glycinergic innervation to the murine LSO and SPN in the presence and absence of the MNTB - Altieri, Stefanie C.; Zhao, Tianna; Jalabi, Walid; Maricich, Stephen M. (Frontiers in Neural Circuits, 2014)
Neurons in the superior olivary complex (SOC) integrate excitatory and inhibitory inputs to localize sounds in space. The majority of these inhibitory inputs have been thought to arise within the SOC from the medial nucleus of the trapezoid body (MNTB). However, recent work demonstrates that glycinergic innervation of the SOC persists in Egr2; En1CKO mice that lack MNTB neurons, suggesting that there are other sources of this innervation (Jalabi et al., 2013). To study the development of MNTB- and non-MNTB-derived glycinergic SOC innervation, we compared immunostaining patterns of glycine transporter 2 (GlyT2) at several postnatal ages in control and Egr2; En1CKO mice. GlyT2 immunostaining was present at birth (P0) in controls and reached adult levels by P7 in the superior paraolivary nucleus (SPN) and by P12 in the lateral superior olive (LSO). In Egr2; En1CKO mice, glycinergic innervation of the LSO developed at a similar rate but was delayed by one week in the SPN. Conversely, consistent reductions in the number of GlyT2+ boutons located on LSO somata were seen at all ages in Egr2; En1CKO mice, while these numbers reached control levels in the SPN by adulthood. Dendritic localization of GlyT2+ boutons was unaltered in both the LSO and SPN of adult Egr2; En1CKO mice. On the postsynaptic side, adult Egr2; En1CKO mice had reduced glycine receptor α1 (GlyRα1) expression in the LSO but normal levels in the SPN. GlyRα2 was not expressed by LSO or SPN neurons in either genotype. These findings contribute important information for understanding the development of MNTB- and non-MNTB-derived glycinergic pathways to the mouse SOC.